ANALISIS HASIL BELAJAR IPA DITINJAU DARI GAYA BELAJAR PADA MODEL PROJECT BASED LEARNING BERBANTUAN KARTU MASALAH” - Dewi Fitriana (Tunas Nusantara, 2023)
Learning style must receive adequate consideration so that teachers could determine specific learning model or media. Teachers that could not pay attention on this aspect would likely fail to bring their students in achieving the targeted learning objective. Therefore, teachers should not perceive all learning styles had to be the same but instead teachers should perceive the varieties of the learning styles as the students’ needs. This descriptive qualitative research analyzed the science learning outcomes based on the learning styles with the assistance of card problems and project-based learning model. The researchers took the population from SDN Purwoyoso 04 Semarang with purposive sampling. The results were 24 students of 5A class. The researchers collected the data with haunted learning styles, science test questions, and observation. The results showed that learning style and influenced the science learning outcomes.